Effect of magnetic field on brush plating Ni–Co alloy. (1st February 2017) - Fang, X.; Cui, X. F.; Jin, G.; Wang, Y.
Abstract : Ni–Co electro-brush plating on stainless steel FV520(b) surface was conducted in a perpendicular magnetic field with different intensities. The effects of the applied magnetic field on surface morphology, alloy microstructure, tribological properties and residual stress were investigated by scanning electron microscope, X-ray diffraction, X-ray photoelectron spectroscopy, mechanical tests and a nanoindentation technique. The results showed that a smoother and more uniform Ni–Co alloy coating layer with less defects could be obtained in magnetic field of high intensity. Furthermore, by increasing the intensity of the magnetic field, the content of Co in the alloy coating and the wear resistance of the coating layers increased, and the residual stress decreased. In addition, the magnetic field had a significant influence on the valence change of Ni and Co. In particular, when the intensity of magnetic field was 0.2 T a coating with best integrated performance was obtained.